Association of CYP3A variants with kidney transplant outcomes. (3rd February 2015) - Traynor, Carol; Conlon, Peter; Phelan, Paul J.; O'Kelly, Patrick; Elens, Laure; McCormack, Mark; Cavalleri, Gianpiero; Comber, Harry; van Schaik, R.H.N.; Conlon, Peter J.
Abstract: Cyclosporine is used extensively in kidney transplantation and is a substrate for cytochrome P450 enzymes. The role of cytochrome p450 polymorphisms in kidney transplant outcome has not yet been fully elucidated. We investigate the clinical impact of single nucleotide polymorphisms in CYP3A4, CYP3A5, PPARα, and POR*28 in 255 kidney transplant recipients. We examine for any association with graft survival, time to first cancer, and delayed graft function, and also measure cyclosporine levels at days 3, 10, and months 1, 3, 6, and 12 after transplantation. The CYP3A4*22 allele is significant associated with the development of cancer post-kidney transplantation (HR 0.20, 95% CI 0.07–0.57, p  = 0.003). It is not significantly associated with graft survival. No other SNP's were associated with graft survival time to first cancer, or delayed graft function. There was a non-significant trend of lower cyclosporine dose requirement in CYP3A4*22 carriers. Independent replication of our findings is now warranted to confirm or reject the role of CYP3A variants in cancer development following kidney transplantation.